Classification of inductive thinking in mathematical problem solving - Kholid, Muhammad Noor; Syafif, Insiana Aribatunnisah (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Inductive thinking is a method of thinking that involves recognizing patterns, understanding relationships, and deconstructing general rules. This method of thinking develops through a variety of factors that support complex problem solving. Using mathematical problems that describe the inductive thinking process within the context of number problems helps investigate students' inductive thinking process. This study, employing a qualitative descriptive research approach, seeks to develop a novel classification framework for students' inductive thinking in the context of mathematical problem solving. The study was conducted in a structured manner on 21 students enrolled in the Department of Mathematics during their fifth semester at a university in Indonesia using number sequence as the problem material. The collection of data was executed through the administration of tests and the observations of problem-solving behaviors. The analysis was conducted using constant comparative procedures (CCP). The instruments used in this study included mathematical problems and recording devices. The findings of this study are presented in the form of three different classifications of inductive thinking: the use of variables, the use of visual, and the use of formulae. The study offers significant theoretical insights for future research and practical implications for the implementation of inductive thinking in improving mathematical problem-solving.